Pedagogical Implications of Service-Learning Integration in Engineering Education - Palpanadan, Sarala @ Thulasi; Ahmad, Iqbal; Isa, Khairunesa; K.Ravana, Venosha (Blue Eyes Intelligence Engineering & Sciences Publication, 2020)
Today, researchers and engineering educators are much concerned about the future of engineering students who do not receive sufficient practical knowledge about their field and its context. Some criticize the issues related to the use of resources and retention while others feel that the teaching practices in terms of effective pedagogy do not match the required learning strategies and approaches of engineering students. Thus, many educators see service-learning as one of the most crucial solution to several problems and issues that arise in the field of engineering education currently. It has been observed that over the years, the curriculum of engineering education has been subjected to fluctuations. Much work exists that focuses on the theoretical aspects of engineering education but less work has been done on the practical aspects of engineering education. In this paper we assess the potential contributions of service-learning in helping out engineering students in developing the required knowledge and skills which are applicable in the field of engineering. The results showed that integration of service-learning in engineering education was found useful for engineering students in many respects. It was found that integrating service-learning into the engineering programme was offered practical learning opportunities, experiences, contexts, and motivation to engineering students. It was further found that service-learning also promoted the goals of engineering education by engaging engineering students in a real life practical learning which enhanced their capability towards problem solving and critical thinking.